The art of political manipulation - Riker, William H. (Yale University Press, 1986)
Riker uses game theory to illustrate political strategy in twelve stories from history and current events, including Lincoln's outmaneuvering of Douglas in their debates and the parliamentary trick which defeated the Equal Rights Amendment in the 1980 Virginia Senate vote.